NORMALIZATION OF ONLINE SHOP PAYMENTS THROUGH THE SHOPEEPAY LATER SERVICE QS PRESPECTIVE ALI IMRAN Verse 130: NORMALIZATION OF ONLINE SHOP PAYMENTS THROUGH THE SHOPEEPAY LATER SERVICE QS PRESPECTIVE ALI IMRAN Verse 130 - Lili Kaina (Taqrib : Journal of Islamic Studies and Education, 2023)
Abstract This study aims to discuss the law of the shopeepay later feature in the Qs perspective shopee application. Ali Imran verse 130 because many people are currently normalizing the shopeepay later service for the payment system at shopee. This study uses a qualitative approach research method using maudhu'i interpretation. Maudhu'i interpretation is a method of interpretation that seeks to find answers to the Qur'an by collecting verses of the Qur'an that have one goal. The results of the discussion of this study indicate that the use of the shopeepay later service contains an element of usury Qard, this occurs because the Shopee Paylater element provides personal benefits for Shopee alone. The public currently has an obligation to avoid using the shopeepay later payment feature in the shopee application. This research is expected to provide benefits as a treasure trove of knowledge about the shopeepaylater feature in a QS perspective. Ali Imran verse 130 so that people at this time can minimize or even avoid using shopeepay later. This research has limitations because it only discusses from one interpreter's point of view and only discusses Qs. Ali Imran verse 130. This study recommends further research with different methods so that the results are more recent, and valid. Keywords: Al-Qur'an, Shopee, Shopeepay later